Deployment of Information Communication for Teaching and Learning of Economics in Public Secondary Schools in Federal Capital Territory, Abuja, Nigeria - N,. J., Ogunode; T. Yemi, Dr. Akin-Ibidiran; Akinbusoye, Ibidiran John (Research Parks Publishing LLC, 2022)
Information Communication Technology is one of the instructional aides available for the implementation of teaching programmed in all educational institutions especially in the public secondary schools. However, the deployment of Information communication technologies for the teaching and learning of Economics in Federal capital seem to be faced with many challenges. This paper discussed the factors hindering effective deployment of ICT for teaching and learning in Federal Capital Territory. Empirical papers on ICT both print and softcopies were collected and used in this paper. The empirical papers were sourced from physical libraries and online. Inadequate funding, inadequate ICT facilities, unstable power supply, poor internet services, high cost of ICT facilities, shortage of ICT expertise, poor implementation of ICT policies, poor implementation of ICT policies, poor ICT literacy of Economics teachers and poor ICT literacy of Economics Students were identified as the factors hindering effective deployment of ICT for teaching and learning of economics in Federal capital Territory, Abuja. To address these problems, the following were recommended; that the government should increase the funding of the ICT programs in all the public secondary schools in Federal Capital Territory, Abuja. This will make funds available for school administrators to purses adequate ICT facilities for students’ use and the government should provide adequate ICT facilities in all public secondary schools in Federal Capital Territory, Abuja. This will provide opportunities for Economics teachers and students to use ICT for teaching and learning in their schools etc.